Direct and Indirect In-Vitro Plant Regeneration and Antioxidant Production in Tsaang Gubat [Carmona retusa (Vahl.) Masam] - Reglos-Zara, Rocelie A.; Cedo, Ma. Lourdes O.; De Guzman, Constancio C.; Rodriguez, Felicito M. (2010)
In vitro plant regeneration of tsaang gubat [Carmona retusa (Vahl.) Masam] via direct and indirect methods using shoot tip explants was studied. The level of antioxidants such as tannin, flavonoids and phenolics in the leaves of in-vitro and field-grown plants was also evaluated. Multiple shoot formation was enhanced when shoot tips were cultured on Murashige and Skoog's (MS) medium containing 5 mg L(-1) 6-benzylaminopurine (BAP). Higher BAP concentration did not induce more new shoots; instead, the original shoot inoculum appeared stunted, vitrified and had abnormally large leaves. Continuous subculturing (6-8 wk) of the regenerated shoots to MS + 5 mg L(-1) BAP and 15% (v/v) coconut water induced shoot proliferation with an average of 15-20 shoots per inoculum after the 3(rd) subculture. MS medium containing 0.5 mg L(-1) naphthaleneacetic acid (NAA) and 4 mg L(-1) BAP was found optimum for callus formation. Subsequent differentiation of shoots was observed only in media containing BAP with the highest number of shoots produced at 10 mgL(-1). Regenerated shoots were successfully rooted on indole-3-butyric acid (IBA)-supplemented medium; the longest and highest number of roots was recorded at 10 mg L(-1) IBA. Levels of phenolics, flavonoids and tannins were higher in the leaves of tissue-culture-raised plants than those of in vivo grown plants. Likewise, plants maintained for long-term (24 wk) under in vitro conditions produced these secondary metabolites, although at lower levels compared with the field-grown materials.
Keywords: Medicinal plants; Regeneration (Biology)